The interactive effects between far-red light and temperature on lettuce growth and morphology diminish at high light intensity - Jeong, Sang Jun; Zhang, Qianwen; Niu, Genhua; Zhen, Shuyang (Frontiers in Plant Science, 2024)
Phytochromes (PHYs) play a dual role in sensing light spectral quality and temperature. PHYs can interconvert between the active Pfr form and inactive Pr form upon absorption of red (R) and far-red (FR) light (Photoconversion). In addition, active Pfr can be converted to inactive Pr in a temperature-dependent manner (Thermal Reversion). Recent studies have shown that FR light and temperature can interactively affect plant growth and morphology through co-regulating phytochrome activities. These studies were primarily conducted under relatively low light intensities. As light intensity increases, the impact of thermal reversion on phytochrome dynamics decreases. However, the light intensity dependency of the interactive effects between FR light and temperature on plant growth and morphology has not been characterized. In this study, lettuce (Lactuca sativa L.) ‘Rex’ was grown under two total photon flux densities (TPFD; 400-800 nm) (150 and 300 μmol m-2 s-1) x three temperatures (20, 24, and 28 ℃) x two light spectra (0 and 20% of FR light in TPFD). Our results showed that the effects of FR light on leaf, stem, and root elongation, leaf number, and leaf expansion were dependent on temperature at lower TPFD. However, the magnitude of the interactive effects between FR light and temperature on plant morphology decreased at higher TPFD. Particularly, at a lower TPFD, FR light stimulated leaf expansion and canopy photon capture only under a cooler temperature of 20 ℃. However, at a higher TPFD, FR light consistently increased total leaf area across all three temperatures. Plant biomass was more strongly correlated with the total number of photons intercepted by the leaves than with the photosynthetic activities of individual leaves. FR light decreased the contents of chlorophylls, carotenoids, flavonoids, and phenolics, as well as the total antioxidant capacity. In contrast, warmer temperatures and high light intensity increased the values of these parameters. We concluded that the interactive effects between FR light and temperature on plant growth and morphology diminished as total light intensity increased. Additionally, the combination of high light intensity, warm temperature, and FR light resulted in the highest crop yield and antioxidant capacity in lettuce.